A study on relationship between employees salary and motivation at Pejabat Pendidikan Daerah Dungun / Nur Hanisah Hassim - Hassim, Nur Hanisah (2017)
This research was tried 10 clarify the relationship between employee's salary and motivation at Pejabat Pendidikan Daerah Dungun by established an integrated framework for employee's salary and motivation. The first objective of this research was to analyse the method for the company to determine the salary for employee while the second objectives of this research was to investigate the relationship between salary and motivation. The sample of this study is supporting staff at Pejabat Pendidikan Daerah Dungun. There are 56 useable questionnaire out of 56 questionnaires were collected from supporting staff at Pejabat Pendidikan Daerah Dungun. The results show that employees' salary has very strong relationship with employees' motivation which is 0.731**. Mostly of respondents for this research are from male and mostly of them are more than 34 years old. The higher education levels of respondents are degree level. Mostly respondents are married and they are from Education Services Officer. Respondents have worked for their current employer for more than 11 years and have experience in current job field for more than 16 years.